Comparison of unilateral and bilateral percutaneous vertebroplasty for osteoporotic vertebral compression fractures: a systematic review and meta-analysis. Issue 1 (December 2016) - Sun, Haolin; Li, Chunde
Abstract Background The aim of this meta-analysis is to examine the safety and effectiveness of unilateral percutaneous vertebroplasty (PVP) for treatment of osteoporotic vertebral compression fractures (OVCFs) compared with that of bilateral treatment. Methods The multiple databases including PubMed, Springer, EMBASE, OVID, and China Journal Full-text Database were adopted to search for relevant studies in English or Chinese, and full-text articles involving comparison of unilateral and bilateral PVP surgery were reviewed. Review Manager 5.0 was adopted to estimate the effects of the results among selected articles. Forest plots, sensitivity analysis, and bias analysis for the articles included were also conducted. Results Finally, 1043 patients were included in the 14 studies, which eventually satisfied the eligibility criteria, and unilateral and bilateral surgeries were 550 and 493, respectively. The meta-analysis suggested that there was no significant difference of VAS score, ODI score, and cement leakage rate (MD = 0.12, 95%CI [−0.03, 0.26], P  = 0.11; MD = −1.28, 95%CI [−3.59, 1.04], P  = 0.28; RR = 0.89, 95%CI [0.61, 1.29], P  = 0.52). The surgery time of unilateral PVP is much less than that of bilateral PVP (MD = −16.67, 95%CI [−19.22, −14.12], P  < 0.00001). Patients with bilateral PVP surgery have been injected more cement than patients with unilateral PVP surgery (MD = −1.55, 95%CI [−1.94, −1.16], P  < 0.00001). Conclusions Both punctures provide excellent pain relief and improvement of life quality. We still encourage the use of the unipedicular approach as the preferred surgical technique for treatment of OVCFs due to less operation time, limited X-ray exposure, and minimal cement introduction and extravasation.